A Stylometric Analysis of the Mar Saba Letter Attributed to Clement of Alexandria. - Tuccinardi, Enrico (Vigiliae Christianae, 2020)
Since the publication of Clement's letter to Theodore, discovered by Morton Smith at Mar Saba, there has been a great deal of controversy surrounding its authenticity. The main aim of the present paper is to weigh the linguistic evidence for and against Clementine authorship of the letter, also checking its alleged excessively Clementine nature in an objective manner, using a profile-based stylometric technique for authorship verification which has proven to be a valuable tool for text of relatively small size. The outcomes of the analysis tend to attribute the disputed letter to Clement but they also show its hyper-Clementine quality. Is this due to a forger, deliberately trying to imitate Clement's style or is it instead a feature characteristic of the epistolary style of Clement? Regrettably without further samples of Clement's letters to be used as terms of comparison it seems not possible to safely answer this question.